Stability of Localized Integral Operators on Normal Spaces of Homogeneous Type. (4th April 2019) - Fang, Qiquan; Shin, Chang Eon
Abstract: The L p -stability of linear operators is one of fundamental concepts in many research fields. In this article, we introduce a family of localized integral operators on a normal space of homogeneous type such that their kernels have some off-diagonal decay, mild singularity near the diagonal and certain Hölder regularity, and we show that localized integral operators in the family have their L p -stability to be equivalent for different exponents 1 ≤ p ≤ ∞ .